BACTERIAL CELLULOSE: ADVANCES AND CHALLENGES (Experimental biology, 2025)
Bacterial cellulose (BC) is a highly pure, crystalline biopolymer synthesized by a variety of microbial species, offering remarkable mechanical strength, high water-holding capacity, and excellent biocompatibility. These unique physicochemical properties have driven extensive research into BC-based materials for biomedical devices, wound dressings, tissue engineering scaffolds, controlled drug delivery systems, sustainable packaging, filtration membranes, and flexible or wearable electronics. Unlike plant-derived cellulose, BC is free from lignin, hemicellulose, and other biomass-associated impurities, resulting in a nanofibrillar network with high crystallinity and tunable porosity. However, despite its advantages, large-scale industrial utilization remains constrained by high production costs, slow fermentation rates, and challenges related to process scale-up and strain stability.Recent strategies to overcome these limitations include the optimization of culture media using agro-industrial residues, bioreactor engineering to enhance oxygen transfer and productivity, co-culture systems to boost metabolic efficiency, and genetic or synthetic biology approaches to reprogram biosynthetic pathways. Additionally, emerging applications such as BC-based composite materials, bioinks for 3D bioprinting, and functionalized scaffolds for regenerative medicine highlight the growing translational potential of BC research. This review provides an integrated overview of BC-producing microorganisms, technological bottlenecks, economic considerations, and current advances aimed at improving scalability, sustainability, and commercial viability. Finally, key outlooks for future innovations and industrial deployment are discussed.
Keywords: bacteria; cellulose; biomass; packaging; residues; challenges